Minor physical anomalies in neurodevelopmental disorders: a twin study - Myers, Lynnea; Bölte, Sven (Child and adolescent psychiatry and mental health, 2017)
Minor physical anomalies (MPAs) are subtle anatomical deviations in one’s appearance and may suggest altered embryogenesis. MPAs have been shown to be more common in neurodevelopmental disorders (NDDs) compared with typical development. Still, further studies are needed on MPAs in NDDs, especially using twins to adjust for confounding familial factors.
Gesehen am 21.11.2018